2021
DOI: 10.3389/fpsyg.2021.708867
|View full text |Cite
|
Sign up to set email alerts
|

Training Emotion Recognition Accuracy: Results for Multimodal Expressions and Facial Micro Expressions

Abstract: Nonverbal emotion recognition accuracy (ERA) is a central feature of successful communication and interaction, and is of importance for many professions. We developed and evaluated two ERA training programs—one focusing on dynamic multimodal expressions (audio, video, audio-video) and one focusing on facial micro expressions. Sixty-seven subjects were randomized to one of two experimental groups (multimodal, micro expression) or an active control group (emotional working memory task). Participants trained once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 77 publications
5
18
0
Order By: Relevance
“…Other factors also influence this task. Döllinger et al (2021) review them, pointing to peer status and friendship quality (Wang et al 2019), to the possible state of depression of the observers (Dalili et al 2015), and to their personality traits (Hall, Mast, and West 2016) -conscientiousness, and openness are positively correlated to the ability to recognize nonverbal expressions of emotions, while shyness and neuroticism are negatively associated with it (Hall, Mast, and West 2016). We also assess personality traits and state-specific variables in our study.…”
Section: Emotion Recognition Reliability In Psychologymentioning
confidence: 99%
“…Other factors also influence this task. Döllinger et al (2021) review them, pointing to peer status and friendship quality (Wang et al 2019), to the possible state of depression of the observers (Dalili et al 2015), and to their personality traits (Hall, Mast, and West 2016) -conscientiousness, and openness are positively correlated to the ability to recognize nonverbal expressions of emotions, while shyness and neuroticism are negatively associated with it (Hall, Mast, and West 2016). We also assess personality traits and state-specific variables in our study.…”
Section: Emotion Recognition Reliability In Psychologymentioning
confidence: 99%
“…In both the pre-test and post-test of micro-expression recognition tasks, we employed the well-accepted paradigm of Japanese and Caucasian Brief Affect Recognition Test (JACBART; e.g., Matsumoto et al, 2000;Hurley, 2012;Hurley et al, 2014;Wu et al, 2016aWu et al, , 2022Demetrioff et al, 2017;Zhang et al, 2020;Döllinger et al, 2021;Fan et al, 2022) to present microexpressions. In this paradigm, a fixation cross was presented for 500 ms at first, after that a facial expression image was presented according to its assigned duration (i.e., 100 ms or 333 ms in Study 1A), which was sandwiched in between two 1 s presentations of the same expresser's neutral face (see Figure 1).…”
Section: Micro-expression Recognition Tasksmentioning
confidence: 99%
“…As far as we know, no previous studies have directly addressed this issue. Answers to this question will deepen our understanding of the micro-expression recognition process which provides the necessary knowledge for developing more efficient micro-expression recognition training programs (Matsumoto and Hwang, 2011;Hurley et al, 2014;Döllinger et al, 2021) or building more valid micro-expression databases (Yan et al, 2014;Yap et al, 2020;Li et al, 2022). In fact, previous studies have found that microexpressions and macro-expressions are usually identical in their appearances (Ekman, 2003;Hwang, 2011, 2018;Yan et al, 2013) and there are some similarities between the recognition of micro-expressions and the recognition of macro-expressions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short duration of micro-expression is not the only obstacle we encountered during micro-expression recognition. To the best of our knowledge, only a few studies have tried to investigate the psychological or brain mechanisms of micro-expression recognition, which makes the scientists difficult to design efficient micro-expression recognition training programs (e.g., Ekman, 2002 ; Frank et al, 2009 ; Matsumoto and Hwang, 2011 ; Döllinger et al, 2021 ). For example, researchers have found that the factors like emotional context, age, childhood family environment, personality, and profession (e.g., Frank et al, 2009 ; Hurley et al, 2014 ; Zhang et al, 2014 , 2020b ; Svetieva and Frank, 2016 ; Demetrioff et al, 2017 ; Felisberti, 2018 ) may affect the recognition accuracy of micro-expressions.…”
Section: Introductionmentioning
confidence: 99%